Cross-national Differences in the Rise in Earnings Inequality - Market and Institutional Factors - Peter Thomas Gottschalk; Mary Joyce (Luxembourg Income Study (LIS), 1997)
This paper uses data from the Luxembourg Income Study to explore the role of differences in supply shifts in explaining cross-national differences in the rise in earnings inequality. Changes in returns to age and education are estimated for eight countries using a common specification of earnings functions across years and countries. It is found that the small overall increase in earnings inequality in many countries reflects large but offsetting changes in returns to skill and changes in inequality within age education cells. Furthermore, these differences in returns to skill can largely be explained by differences in supply shifts.
Keywords: 330